20 years of research on Arctic and Indigenous cultures in Nordic tourism: a review and future research agenda. Issue 1 (1st January 2021) - Ren, Carina; Jóhannesson, Gunnar Thór; Kramvig, Britt; Pashkevich, Albina; Höckert, Emily
ABSTRACT: Through a critical reading of previous research, this article explores local and indigenous cultures in the context of Nordic Arctic tourism and how its consequences have been researched in Nordic tourism research. We show that experiences with, practices of and controversies over the representation and presence (or absence) of local and indigenous culture in tourism take on very many different meanings and shapes across the Nordic Arctic. This, we argue, calls for situated and sensitive ways of doing research. With a focus on Sámi, Nenets in Russia and Greenlandic Inuit, we discuss the current state of indigenous and Arctic culture in Nordic Tourism before looking closer into how Nordic tourism scholarship has addressed the relations between indigenous culture and tourism in the Arctic. We conclude by proposing three trajectories for tourism research and tourism development, which further supplement and diversify ongoing research.